When eyes drive hand: Influence of non-biological motion on visuo-motor coupling. (26th January 2016) - Thoret, Etienne; Aramaki, Mitsuko; Bringoux, Lionel; Ystad, Sølvi; Kronland-Martinet, Richard
Highlights: Visuo-motor coupling of biological motion is examined in visual open-loop. 17 subjects reproduced 3 circular visual motion (1 biological–2 non biological). Non biological kinematics significantly distort the motor reproductions. Motor reproductions significantly amplified the perceptual illusion. Abstract: Many studies stressed that the human movement execution but also the perception of motion are constrained by specific kinematics. For instance, it has been shown that the visuo-manual tracking of a spotlight was optimal when the spotlight motion complies with biological rules such as the so-called 1/3 power law, establishing the co-variation between the velocity and the trajectory curvature of the movement. The visual or kinesthetic perception of a geometry induced by motion has also been shown to be constrained by such biological rules. In the present study, we investigated whether the geometry induced by the visuo-motor coupling of biological movements was also constrained by the 1/3 power law under visual open loop control, i.e. without visual feedback of arm displacement. We showed that when someone was asked to synchronize a drawing movement with a visual spotlight following a circular shape, the geometry of the reproduced shape was fooled by visual kinematics that did not respect the 1/3 power law. In particular, elliptical shapes were reproduced when the circle is trailed with a kinematics corresponding to an ellipse. Moreover, the distortions observed here were larger than in the perceptual tasks stressing the role of motor attractors in such a visuo-motor coupling. Finally, by investigating the direct influence of visual kinematics on the motor reproduction, our result conciliates previous knowledge on sensorimotor coupling of biological motions with external stimuli and gives evidence to the amodal encoding of biological motion.